Common attractive points theorems of widely more generalized hybrid mappings in hilbert spaces - Panadda Thongpaen (2020)
© 2020 by TJM. All rights reserved. We prove existence and weak convergence theorems for common attractive points of two widely more generalized hybrid mappings in Hilbert spaces. Consequently, we obtain a weak convergence theorem for common fixed points of two such mappings.